Knit hats with Woolly Wormhead : styles for the whole family - Woolly Wormhead (Stackpole Books, an imprint of Rowman & Littlefield Publishing Group, Inc., 2021)
"International hat-knitting icon Woolly Wormhead is known for her unique, innovative hat designs. This collection of her work includes patterns for 22 of her designs"--